New record of Govenia purpusii (Orchidaceae) in La Malinche National Park, Tlaxcala, Mexico - Pérez Alva, Braulio Ricardo; Pérez Flores, Guillermo Alejandro (Instituto de Ecología, A.C., 2020)
Background and Aims: Govenia purpusii is a species of the Orchidaceae family; it has a restricted distribution within subalpine forests of the states of Chiapas, Colima, Durango, Guerrero, Hidalgo, Jalisco, Mexico, Michoacán, Oaxaca, Puebla, Querétaro, Veracruz and Zacatecas. The aim of this study was to describe the discovery of this species in La Malinche National Park, Tlaxcala to include it in the floristic inventory.Methods: A population of G. purpusii was identified in the field and collections were made. Through the comparison of botanical material collected with herbarium specimens, the species was determined considering vegetative and floral characters for its identification.Key results: The species was found in Quercus-Pinus vegetation at 2780 m altitude, sharing space with Selaginella sp., Oxalis sp., Peperomia sp. and Pinguicula moranensis.Conclusions: Monitoring this population is recommended due to the small distribution area in La Malinche National Park and the limited knowledge of this population, local extinction would represent a loss of genetic material for the species. This record should not be interpreted as a recent extension in its range, the presence within this area may be the result of forest fragmentation in the Trans-Mexican Volcanic Belt.